Maria Isabel Andrade: Sweetpotato breeder, technology transfer, specialist and advocate - Low, Jan W.; Carey, E.E. (Wiley, 2019)
Dr. Maria Isabel Andrade has not followed the more typical path of being a breeder in an academic institution or a private company. She developed a passion for a crop long neglected by the world, sweetpotato, in large part because it is a crop of the poor, predominantly cultivated by women in Sub‐Saharan Africa. Hence, to be able to breed, she had to become on advocate for the crop, demonstrating its practical potential to not only address food insecurity but that the orange types, largely unknown in Sub‐Saharan Africa (SSA), could also effectively tackle vitamin A deficiency. Most of her career has been spent in Mozambique, where her tireless efforts to develop and deliver improved drought‐tolerant orange‐fleshed sweetpotato varieties have been a model for others to emulate. Her ability to recognize the importance of collaborating with nutritionists and agricultural economists to develop innovative mechanisms to ensure that the improved orange‐fleshed varieties could make a difference to human health and wealth has resulted in growing awareness and recognition of the concept of biofortification, that is breeding for enhance micronutrient quality in staple crops. As a collaborative member of the breeding team at the International Potato Center, she has demonstrated that an innovative accelerated breeding scheme could effectively deliver quality varieties. Over the years, she has mentored hundreds of staff members and students, helping to build a community of practice that recognizes that for scientists to make a difference in SSA, they must stretch their mandate and engage in delivery and often advocacy. This chapter describes the evolution of this unique career of a most amazing woman driven by her faith in god and the power of agriculture to improve nutrition among those most in need.